Analisis Transparansi Keuangan Daerah Melalui Pengungkapan Laporan Keuangan di Internet Saat Pandemi Covid-19 - Khafid Fitriyanto Albahrudin; Hendrawan Santosa Putra; Oktaviani Ari Wardhaningrum (Politeknik Negeri Jember, 2023)
Transparency is an important pillar of government accountability. A transparent government is a government that is accountable and provides information to the public regarding its strategy, plans and performance. This study aims to analyze the effect of audit opinion, independence ratio, and government size on internet financial reporting during the Covid-19 pandemic. The research sample consists of 88 district/city governments in the Java Island region for 2020-2021, using cluster sampling and logistic regression analysis. The results of this study indicate that the independence ratio has an effect on internet financial reporting during the Covid-19 pandemic, while audit opinions and size government have no effect on internet financial reporting during the Covid-19 pandemic.